METHODOLOGY FOR DEVELOPING VOCAL PERFORMANCE SKILLS IN MUSIC TEACHERS - Kavilova, Dilyorakhon (Oriental Journal of Education, 2025)
This article discusses the historical formation and improvement of methods for developing vocal performance skills. It analyzes sound production, singing techniques, pedagogical concepts, and the activities of prominent vocal pedagogues from ancient civilizations to the era of the Italian vocal school. The study also highlights the emergence of new genres and styles, as well as the significance of mixed breathing techniques in vocal art.